2010
DOI: 10.1002/cphc.201000139
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the CC Bond in the Ethanol Oxidation Reaction on Platinum Electrodes: Effect of Steps and Ruthenium Adatoms

Abstract: Ethanol is a possible candidate to use in fuel cells and, for that reason, the study of its oxidation has deserved much attention during the last decade.[1] When compared to methanol, it presents some advantages: it can be obtained directly from biomass distillation, it has a higher energy density since 12 electrons are exchanged in the complete oxidation to CO 2 and it is less toxic. The activity of platinum electrodes, which is the best pure metal for the oxidation of both methanol and ethanol, is similar, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(135 citation statements)
references
References 13 publications
5
129
1
Order By: Relevance
“…The large difference in the reactivity of the steps in the (111) terrace with respect to the terrace sites explain why the M a n u s c r i p t 17 reactivity of the real Pt(111) electrode is, for some reactions, governed by the number of defects, which behave in a similar way to step sites. Thus, it has been proposed that some reactions on a real Pt(111) electrode occurs only on the defects, such as CO oxidation [62], CO formation from formic acid [19,20] or the cleavage of the C-C bond in ethanol oxidation [15,16]. Since those reactions does not occur on the ideal Pt(111) plane, the number of defects clearly affects the reactivity, and significant differences can be observed between Pt(111) electrodes with different quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large difference in the reactivity of the steps in the (111) terrace with respect to the terrace sites explain why the M a n u s c r i p t 17 reactivity of the real Pt(111) electrode is, for some reactions, governed by the number of defects, which behave in a similar way to step sites. Thus, it has been proposed that some reactions on a real Pt(111) electrode occurs only on the defects, such as CO oxidation [62], CO formation from formic acid [19,20] or the cleavage of the C-C bond in ethanol oxidation [15,16]. Since those reactions does not occur on the ideal Pt(111) plane, the number of defects clearly affects the reactivity, and significant differences can be observed between Pt(111) electrodes with different quality.…”
Section: Discussionmentioning
confidence: 99%
“…For the surfaces vicinal to the (111) stereographic pole, that is, those containing terraces with (111) symmetry, significant effects in reactivity of the surface have been found. For those surfaces, the step sites are the active sites on these surfaces for the oxidation of adsorbed CO [14], the cleavage of the C-C bond in the ethanol oxidation reaction [15][16][17][18], or the formation of CO in the formic acid oxidation reaction [19][20][21], whereas the (111) terrace sites have a negligible activity for those processes. On the other hand, for the surfaces vicinal to the (100) pole, the reactivity of the (100) domains is much less affected by the presence of the steps.…”
Section: Page 3 Of 29mentioning
confidence: 99%
“…Platinum single crystal working electrodes preparation, reagents and experimental procedures, including FTIR set-up, is the same as described in previous papers [1][2][3][4][5][6]. Pt(111) and its vicinal surfaces Pt(S)[n(111)x(100)], with Miller indices Pt(n+1, n-1, n-1) and Pt(S)[n(111)x(111)] or Pt(S)[(n-1)(111)x(110)], with Miller indices Pt(n, n, n-2), where n is the number of terrace rows, were used.…”
Section: Methodsmentioning
confidence: 99%
“…This single crystal contains the most compact arrangement of surface atoms and is expected to be an important fraction of surface sites in platinum nanoparticles. The inclusion of steps in the structure leads to a better performance, because C-C breaking takes place at steps [2,3]. In contrast, EG seems to effectively dissociate at platinum, in such a way that CO was considered to be the only relevant residue from spontaneous interaction of the fuel with the different basal planes [4].…”
Section: Introductionmentioning
confidence: 99%
“…According to these authors on Pt(111) terraces ethanol oxidation occurs via acetaldehyde to acetic acid and only a small CO 2 fragment is observed. In the case of Pt (110) Pt (111) Pt (110) Pt (110) Pt (100) In addition, it is also possible to modify SCE surfaces with adatoms of another metal [101][102][103][104] and these electrodes are of special interest because they resemble bimetallic nanoparticles that will be discussed in Section 5.4. For instance addition of Ru atoms on Pt(332) surface revealed that Ru has only an active role in the oxidation of CO ads to CO 2 , but has no role in enhancement of -CH 3 transformation to CO nor C-C bond cleavage [101].…”
Section: Figure 19 Low-index Planes (100) (111) and (110) Of Fcc Symentioning
confidence: 99%